Multiscale Study on Deterioration Characteristics of Soil-Rock Mixtures Under the Immersion-Air dry Circulation - Li, Li; Zhang, Shixin; Qiang, Yue; Xia, Xiaozhou; Li, Shaohong; Chen, Longfei (Frontiers in Earth Science, 2022)
Soil-rock mixtures (S-RMs) composed of rock slope colluvium and landslide deposits are common in superficial hazards of bank slopes. The physical and mechanical properties of S-RMs are closely related to environmental conditions, especially reservoir water level fluctuation. Therefore, immersion-air dry (I-AD) circulations tests were carried out to simulate the phenomenon in this study. The macroscopic, mesosopic, and microcosmic studies of S-RMs are carried out after experiencing cycles (N) of 0, 1, 5, and 10, respectively. Conventional triaxial tests, particle analysis tests, and scanning electron microscopy were performed to study the physical and mechanical properties of S-RMs. According to test results, the maximum deviator stress of S-RMs samples with confining pressures of 100 kPa, 200 kPa, 300 kPa, and 400 kPa after ten cycles is reduced by 41.13%, 37.11%, 32.17%, and 30.20%. With the increase in N there is a significant trend towards reducing the strength of S-RMs, and the strength deterioration after the first I-AD circulation reached 15.73%. After I-AD circulations, the content of fine particles in S-RMs decreases, the grain-size characteristic and non-uniformity coefficient increase significantly, and the gradation of S-RMs shows discontinuity. Moreover, the repeated changes of water pressure have an irreversible impact on the microstructure of S-RMs, which will cause an increase in pore size and a higher pore disorder. In addition, it is found from the established strength parameter evolution equation that when N approaches infinity, S-RMs decomposes the weathering into cohesionless silt with an angle of repose of 0.903220.